Are instructional practices different between East and West? An analysis of Grade 8 TIMSS 2019 data. Issue 2 (June 2022) - Bokhove, Christian
After each round of International Large-scale Assessments such as the Trends in International Mathematics and Science Study (TIMSS) and the Programme for International Student Assessment (PISA), excellent achievements by countries in East Asia are explained in terms of their instructional practices. However, instructional practices are not easily captured in self-reported scales. In addition, speculations on what approaches lead to the highest mathematics achievement are often combined and conflated with discussions on how mathematical content needs to be taught. This article reports on a secondary analysis of TIMSS 2019 Grade 8 data from 46 jurisdictions of teacher-reported answers on instructional practices. Using a data-driven exploratory factor analysis, three instructional scales are compiled and supplemented with variables on barriers to instruction and instructional time. Multilevel models of all countries are created for students and teachers, in which the relationship between these instructional practices and mathematics achievement is explored. Across countries, the results show that the three new scales for instructional practice work in limited and different ways, but that barriers toward instruction, and to a lesser extent, instructional time, predict mathematics achievement. However, there is no consistent pattern of instructional practices across all countries, and also not among East Asian countries.